The transformation of black music the rhythms, the songs, and the ships of the African diaspora - Floyd, Samuel A. Jr. 1937-2016; Zeck, Melanie; Ramsey, Guthrie P. (Oxford University Press, 2017)
Powerful and embracive, "The Transformation of Black Music"explores the full spectrum of black musics over the past thousand years as Africans and their descendants have traveled around the globe making celebrated music both in their homelands and throughout the Diaspora. Authors Samuel A. Floyd, Melanie Zeck, and Guthrie Ramsey brilliantly discuss how the music has blossomed, permeated present traditions, and created new practices. As a companion to the ground-breaking The Power of Black Music, this text brilliantly situates emerging, morphing, and influential black musics in a broader framework of cultural, political, and social histories. Grappling with subjects frequently omitted from traditional musical texts, "The Transformation of Black Music" is guided by more than just the ideals of inclusivity and representation. This work covers overlooked topics that include classical musicians of African descent, and builds upon the contributions of esteemed predecessors in the field of black music study. Providing a sweeping list of figures rarely included in conventional music history and theory textbooks, the text elucidates the findings of ethnomusicologists, cultural historians, Americanists, Africanists, and anthropologists, and weaves these accounts into a powerful and informative narrative. Taking its readers on a journey - one that has never been attempted in a single volume alone - this book reflects the musical phenomena generated by forced African migration and collective memory, and considers the kinds of powerful stories that these musics were meant to tell. Filling in critical musical and historical gaps previously ignored, authors Floyd, Zeck, and Ramsey infuse an engaging musical dialogue with a deeper understanding of the interrelationships between black musical genres and mainstream music.